Geometric and Harmonic Structures in Nature and Art - Cristian Ungureanu (Anastasis: Research in Medieval Culture and Art)
Book review: Ioan Pricop, Geometric and Harmonic Structures in Nature and Art, Artes Publishing House, Iași, 252 pages.